Unfolded Protein Response Differentially Regulates TLR4-Induced Cytokine Expression in Distinct Macrophage Populations - Zhang, Lei; Pavicic, Paul G.; Datta, Shyamasree; Song, Qiaoling; Xu, Xiaohan; Wei, Wei; Su, Fan; Rayman, Patricia A.; Zhao, Chenyang; Hamilton, Thomas (Frontiers in Immunology, 2019)
Cellular stress responses are often engaged at sites of inflammation and can alter macrophage cytokine production. We now report that macrophages in distinct states of differentiation or in different temporal stages of inflammatory response exhibit differential sensitivity to cell stress mediated alterations in M1-like polarized inflammatory cytokine production. Tunicamycin (Tm) treatment of bone marrow derived macrophages (BMDM) cultured with M-CSF (M-BMDM) had markedly amplified M1-like responses to LPS, exhibiting higher levels of IL12p40 and IL12p35 mRNAs while BMDM cultured with GM-CSF, which normally express high IL12 subunit production in response to LPS, were relatively unaltered. Anti-inflammatory IL10 mRNA production in LPS-stimulated M-BMDM was greatly reduced by cell stress. These changes in cytokine mRNA levels resulted from altered rates of transcription and mRNA decay. Stress also altered cytokine protein production. Resident liver macrophages isolated from mice treated with Tm showed elevated levels of IL12 subunit mRNA production following LPS stimulation. Furthermore, macrophages infiltrating the liver during the early phase of acetaminophen injury (24 hrs) had little stress-mediated change in cytokine mRNA production while cells isolated in the later phase (48-72 hrs) exhibited higher sensitivity for stress elevated cytokine production. Hence cultured macrophages developed using different growth/differentiation factors and macrophages from different temporal stages of injury in vivo show markedly different sensitivity to cell stress for altered inflammatory cytokine production. These findings suggest that cellular stress can be an important modulator of the magnitude and character of myeloid inflammatory activity.